The Impact of COVID-19 on the Cost of Living in Malaysia - Nornasirah Ahmad Hasran @ Kamarulzaman; Nurul Sima Mohamad Shariff; Sharifah Fairuz Syed Mohamad; Aldo Eko Syaputra (Karya Ilham Publishing, 2026)
Non-Indexed Publication